2013
DOI: 10.1021/ct400647w
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of Stilbene: The Detailed XMCQDPT2 Treatment

Abstract: We report the detailed XMCQDPT2/cc-pVTZ study of trans-cis photoisomerization in one of the core systems of both experimental and computational photochemistry-the stilbene molecule. For the first time, the potential energy surface (PES) of the S1 state has been directly optimized and scanned using a multistate multiconfiguration second-order perturbation theory. We characterize the trans-stilbene, pyramidalized (phantom), and DHP-cis-stilbene geometric domains of the S1 state and describe their stationary poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
149
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(162 citation statements)
references
References 155 publications
9
149
2
Order By: Relevance
“…In this sense, the torsional barrier around the vinylene moiety (dihedral angle α ) was calculated for all studied compounds in the S 1 excited state to deepen our understanding of its role in E / Z photoisomerization as a nonradiative deactivation process (see Figure ).Obtaining a complete description of the potential energy surface of the S 1 state of these compounds is out of the scope of the current study and could become extremely complex and prohibitively demanding (see ref. and references therein). Nevertheless, in the scanned region (from α =0 to 45°), it was found that the energy required for this rotation was significantly higher for compound 2 than that for 1 , according to the lower efficiency expected for E / Z photoisomerization of the tetrabranched molecule as a nonradiative deactivation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the torsional barrier around the vinylene moiety (dihedral angle α ) was calculated for all studied compounds in the S 1 excited state to deepen our understanding of its role in E / Z photoisomerization as a nonradiative deactivation process (see Figure ).Obtaining a complete description of the potential energy surface of the S 1 state of these compounds is out of the scope of the current study and could become extremely complex and prohibitively demanding (see ref. and references therein). Nevertheless, in the scanned region (from α =0 to 45°), it was found that the energy required for this rotation was significantly higher for compound 2 than that for 1 , according to the lower efficiency expected for E / Z photoisomerization of the tetrabranched molecule as a nonradiative deactivation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, they are divided into Z ‐type and E ‐type based on the configuration of their central double bond; this can undergo Z / E isomerization, changing the overall configuration and decreasing the biological activity. In fact, photoisomerization is a problem that represents a common challenge in optimization work and most quantum chemistry calculation research has focused on its mechanisms but has not been concerned with optimizing these compounds to improve their stability and maintain their biological activity …”
Section: Introductionmentioning
confidence: 99%
“…Stilbenes are abundant in naturalp roducts [4] with av ariety of importantb iological activities. [5] Structurally,t hey are divided into Z-type and E-type based on the configuration of their central double bond;t his can undergo Z/E isomerization,c hanging the overall configuration and decreasing the biological activity.I nf act, photoisomerization is ap roblem that represents ac ommon challenge in optimization work and most quantum chemistry calculation research has focused on its mechanisms [6] but has not been concerned with optimizing these compounds to improvet heir stability and maintain their biological activity. [7][8][9] Stilbene containing compounds have drawn the attentiono f chemists and pharmacologistso vert he years mainly because of their important biological properties, such as antioxidant, hypolipidemic, antiviral, anti-inflammatory and anticancer.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 So we will check if the relationship found in fluorene-based ethylenoids is also true for simple ethylenoids such as ethylene, styrene and stilbene in Figure 1. The CIXs of these ethylenoids, which have been extensively studied, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] are geometrically characterized by a non-symmetrical pyramidalized geometry; i) the C=C double bond is perpendicularly twisted, ii) the local geometry around the anionic C atom of the ethylenic bond is pyramidal and the other is planar, iii) the pyramidal structure is highly skewed against the ethylenic bond. By virtue of explicit definitions by internal coordinates, the CIXs are characterized by a geometry where the ethylenic double bond is perpendicularly twisted and in addition anionic portion of the ethylidenes is highly wagged and rocked against the ethylenic bond.…”
Section: Introductionmentioning
confidence: 99%